The Relationship Between Ethical Priciples, Job Satisfaction, And Psychological Empowerment With Organizational Citizenship Behavior Among Private Hospitals Staff Members In Shiraz - Mohammad Ali Nadi; Nilofar Moghtaderi (Tehran University of Medical Sciences, 2015)
Background and Aim: Based on theories and researches, three variables effective in the organizational citizenship behavior are e thical values, job satisfaction and psychological empowerment. The present study aims to explore the relationship between these variables and the organizational citizenship behavior (OCB) among the staff members of private hospitals in Shiraz. Materials and Methods: This is a cross-sectional correlational study. Some 330 staff members (147 males and 183 females) were selected using stratified sampling technique. The data collection devices consisted of five standardized questionnaires, the reliability of which turned out to be 0.85, 0.93, 0.70, 0.89, 0.90 and 0.70 Besides, the construct validity was confirmed through factor analysis. The data were analyzed inferentially using Pearson's correlation test, stepwise regression analysis and SEM. Results: The findings revealed that there was a significant positive correlation between ethical principles, psychological empowerment and job satisfaction with organizational citizenship behavior (p<0/001). Moreover, the findings of stepwise regression analysis showed that ethical climate played a significant role in predicting OCB. Conclusion: The staff members' effort to enhance OCB is mostly influenced by psychological empowerment in private hospital.